2012
DOI: 10.1371/journal.pone.0049398
|View full text |Cite
|
Sign up to set email alerts
|

Active Sulforhodamine 101 Uptake into Hippocampal Astrocytes

Abstract: Sulforhodamine 101 (SR101) is widely used as a marker of astrocytes. In this study we investigated labeling of astrocytes by SR101 in acute slices from the ventrolateral medulla and the hippocampus of transgenic mice expressing EGFP under the control of the astrocyte-specific human GFAP promoter. While SR101 efficiently and specifically labeled EGFP-expressing astrocytes in hippocampus, we found that the same staining procedure failed to label astrocytes efficiently in the ventrolateral medulla. Although carbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 49 publications
3
62
0
Order By: Relevance
“…It has been shown that hippocampal astrocytes can be efficiently labeled with SR101, but the uptake system involved had been unknown. 56) However, Hülsmann's group has recently clarified that SR101-labelling intensity is severely reduced in the presence of rifampicin and dehydroepiandrosterone sulfate, which are OATP substrates/inhibitors, 57) and SR101-labelled astrocytes mostly disappeared in Oatp1c1-knockout mice. 58) OATP1C1 is a multi-specific organic anion transporter, but its primary substrates are thyroid hormones, with the highest activity towards 3,5,3′,5′-tetraiodothyronine (thyroxine, T4).…”
Section: Organic Anion Transportersmentioning
confidence: 99%
“…It has been shown that hippocampal astrocytes can be efficiently labeled with SR101, but the uptake system involved had been unknown. 56) However, Hülsmann's group has recently clarified that SR101-labelling intensity is severely reduced in the presence of rifampicin and dehydroepiandrosterone sulfate, which are OATP substrates/inhibitors, 57) and SR101-labelled astrocytes mostly disappeared in Oatp1c1-knockout mice. 58) OATP1C1 is a multi-specific organic anion transporter, but its primary substrates are thyroid hormones, with the highest activity towards 3,5,3′,5′-tetraiodothyronine (thyroxine, T4).…”
Section: Organic Anion Transportersmentioning
confidence: 99%
“…Our preliminary experiments conducted on the brain slice preparation loaded with sulforhodamine 101, an astrocyte specific dye (Schnell, Hagos & Hulsmann. ), showed very small swelling during exposure to hypotonic ACSF (Supplementary Figure ). We are studying the behavior of astrocytes under hypotonic stress to confirm their minor contribution to brain edema.…”
Section: Discussionmentioning
confidence: 99%
“… Supplemental Fig.1 Preliminary examination on the contribution of astrocytes to the edema in the brain slice during hypotonic stress . A: The response to hypo‐ACSF exposure of a mouse brain slice loaded with a lower concentration (1 μM) of sulforhodamine 101, which was reported to be specifically taken up into astrocytes (Schnell et al ). Only a small transient decrease in the fluorescence intensity was observed during 10 min of the exposure to hypo‐ACSF in both the LCC and CA1 regions.…”
mentioning
confidence: 99%
“…SR101 is a highly specific and widely used tool for the identification of mature astrocytes in many brain regions including the hippocampus [29, 30]. It has recently been shown to be taken up into mature hippocampal astrocytes via an active transport mechanism involving organic anion transport polypeptides [31]. Wide-field fluorescence imaging was performed using a variable scan digital imaging system (TILL Photonics, Martinsried, Germany) attached to an upright microscope (BX51Wi, Olympus Europe, Hamburg, Germany) and a CCD camera (TILL Imago VGA, Till Photonics, Martinsried, Germany).…”
Section: Methodsmentioning
confidence: 99%